Implementation of the TOSS-TB Program at Sungai Durian Community Health Center, Kubu Raya Regency - Irna Valia; Arkanudin Arkanudin; Annisa Rizqa Alamri; Zahra Sagita; Rivella Irene; Mita Yuniarti; Agnes Nova Triyanasrani (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
The high number of Tuberculosis (TB) cases in Indonesia causes social paralysis in the community. Therefore, the TOSS-TB program is designed to alleviate and break the chain of spread of Tuberculosis (TB) throughout Indonesia. This study aims to analyze the implementation of the TOSS-TB program, especially at the Sungai Durian Community Health Center. The Working Area of the Sungai Durian Community Health Center, which is a tropical area, is the main factor that has quite potential in the development of several disease germs, so researchers are interested in making the Sungai Durian Community Health Center a research subject in the implementation of the TOSS-TB program. Implementation analysis based on Edward III's implementation theory assesses the success of the program through four aspects, namely resources, communication, bureaucracy, and disposition. The method in this study uses a qualitative descriptive approach with data collection techniques in the form of purposive sampling. The results showed that the implementation of the TOSS-TB program at the Sungai Durian Community Health Center in the aspects of communication, disposition, and bureaucracy had met the criteria. However, the resource aspect is still constrained in terms of facilities and infrastructure.